2020
DOI: 10.1111/pbi.13502
|View full text |Cite
|
Sign up to set email alerts
|

Identification of citrus immune regulators involved in defence against Huanglongbing using a new functional screening system

Abstract: Summary Huanglongbing (HLB) is the most devastating citrus disease in the world. Almost all commercial citrus varieties are susceptible to the causal bacterium, Candidatus Liberibacter asiaticus (CLas), which is transmitted by the Asian citrus psyllid (ACP). Currently, there are no effective management strategies to control HLB. HLB‐tolerant traits have been reported in some citrus relatives and citrus hybrids, which offer a direct pathway for discovering natural defence regulators to combat HLB. Through compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…There are seven species of Australian limes that are all native to Australia and the New Guinea islands (Forster and Smith, 2010). Australian lime species such as Citrus australasica, and the hybrid of Citrus australis and Citrus virgata (Sydney hybrid) have been reported to be HLB resistant (Ramadugu et al, 2016;Alves et al, 2020;Huang et al, 2021a). Thus, these species can provide pathogen resistancerelated genes that can be used to confer HLB tolerance into conventional citrus cultivars to produce HLB-tolerant citrus hybrid scions and rootstocks.…”
Section: Introductionmentioning
confidence: 99%
“…There are seven species of Australian limes that are all native to Australia and the New Guinea islands (Forster and Smith, 2010). Australian lime species such as Citrus australasica, and the hybrid of Citrus australis and Citrus virgata (Sydney hybrid) have been reported to be HLB resistant (Ramadugu et al, 2016;Alves et al, 2020;Huang et al, 2021a). Thus, these species can provide pathogen resistancerelated genes that can be used to confer HLB tolerance into conventional citrus cultivars to produce HLB-tolerant citrus hybrid scions and rootstocks.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar Belle contained high level of secondary metabolites such as volatile organic compounds (VOC), phenolics, and flavonoids (Killiny et al, 2017;Hijaz et al, 2020;Deng et al, 2021;Huang et al, 2021b).…”
Section: Activation Of Antimicrobial Metabolitesmentioning
confidence: 99%
“…In addition, amino acids including phenylalanine, tyrosine, and tryptophan were accumulated on HLB-tolerant citrus relative P. trifoliata ( Killiny and Hijaz, 2016 ), which are involved in synthesis of many secondary metabolites. Furthermore, several studies demonstrated that HLB-tolerant citrus including US-942 ( P. trifoliata×Citrus reticulata ), Curry leaf [ Murraya koenigii (L.) Spreng], and LB8-9 Sugar Belle contained high level of secondary metabolites such as volatile organic compounds (VOC), phenolics, and flavonoids ( Killiny et al, 2017 ; Hijaz et al, 2020 ; Deng et al, 2021 ; Huang et al, 2021b ).…”
Section: Activation Of Antimicrobial Metabolitesmentioning
confidence: 99%
“…trifoliata × C . reticulata ) and a susceptible citrus variety identified a panel of candidate defense regulators for plant immune responses against HLB, such as the positive regulator BRCA1-associated protein and the negative regulator vascular-associated death protein [ 172 ]. C Las infection and D .…”
Section: Improvements For Hlb Tolerancementioning
confidence: 99%